Monocytic TLR4 expression and activation in schizophrenia: A systematic review and meta-analysis. - Melika Jameie; Sanaz Bordbar; Reza Samiee; Mobina Amanollahi; Mehdi Azizmohammad Looha; Mir Sajjad Aleyasin; Mohammad Reza Abdol Homayuni; Mehrdad Mozafar; Seyed Behnamedin Jameie; Shahin Akhondzadeh (PLoS ONE)
Background The role of toll-like receptor 4 (TLR4) in schizophrenia remains unclear, with studies reporting conflicting results on its expression and activation in persons with schizophrenia (PwSCZ). This systematic review/meta-analysis compared basal monocytic TLR4 expression, as well as its activation pattern between PwSCZ and healthy controls (HCs). Methods This study was registered with PROSPERO (CRD42021273858) and adhered to the PRISMA guidelines. A systematic search was conducted through MEDLINE (via PubMed), Web of Science, and Scopus from inception to December 12, 2023. Quantitative syntheses were conducted for (a) basal monocytic TLR4 density, (b) basal percentage of TLR4+ monocytes, and (c) basal TLR4 gene expression. Effect sizes were computed using Hedges' g for mean differences. Random-effect models with restricted maximum-likelihood estimation were used, and subgrouping was conducted based on antipsychotic status. The studies' risk of bias was assessed using the Joanna Briggs Institute (JBI) tool. Results Eleven studies (473 PwSCZ, 416 HCs) were included. Pooled analysis revealed a nonsignificant trend toward increased basal monocytic TLR4 density in PwSCZ (Hedges' g = 0.317 [95% CI: -0.060, 0.694], τ2 = 0.127, I2 = 68.91%). The difference became significant after sensitivity analysis and excluding one study (Hedges' g = 0.469 [0.195,0.742], p = 0.001). No significant difference was found between the groups in terms of TLR4+ monocytes percentage (Hedges' g = 0.235 [-0.245, 0.715], τ2 = 0.31, I2 = 87.30%) or TLR4 gene expression (Hedges' g = 0.179 [-0.502, 0.861], τ2 = 0.29, I2 = 79.04%). According to qualitative synthesis, TLR4 stimulation resulted in reduced monocytic activation in PwSCZ compared to HCs. Conclusions This study suggested a trend toward an increased basal monocytic TLR4 density in PwSCZ, with no difference in the basal percentage of TLR4+ monocytes or TLR4 gene expression. However, the limited available data underscores the need for future studies.